2021
DOI: 10.3390/genes12030427
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impacts of Interleukin-17A Promoter Polymorphisms on the EGFR Mutation Status and Progression of Non-Small Cell Lung Cancer in Taiwan

Abstract: Non-small cell lung cancer (NSCLC) is a typical inflammation-associated cancer, and lung adenocarcinoma (LUAD) is the most common histopathological subtype. Epidermal growth factor receptor (EGFR) mutations are the most common driver mutations of LUAD, and they have been identified as important therapeutic targets by EGFR tyrosine kinase inhibitors. Interleukin (IL)-17A secreted by T-helper 17 lymphocytes is a proinflammatory cytokine that plays an important role in cancer pathogenesis. The present study was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…Our observation that EGFR mutations are more common in females than males and in never-smokers than in ever-smokers among patients with LUAD is consistent with previous reports [ 6 , 29 ]. We also found that EGFR wild-type disease was more likely to exhibit poor cell differentiation and lower rates of well or moderate cell differentiation compared to EGFR -mutant disease, which is consistent with previous reports [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our observation that EGFR mutations are more common in females than males and in never-smokers than in ever-smokers among patients with LUAD is consistent with previous reports [ 6 , 29 ]. We also found that EGFR wild-type disease was more likely to exhibit poor cell differentiation and lower rates of well or moderate cell differentiation compared to EGFR -mutant disease, which is consistent with previous reports [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…Given the important role of EGFR mutation status in NSCLC development, we decided to explore interactions amongst crucial genes and EGFR status in NSCLC and LUAD. Interleukin-17A, the tumor suppressor protein WW domain-containing oxidoreductase, tissue inhibitor of metalloproteinase 3 (TIMP3), and long noncoding RNA H19 polymorphisms have all been associated with clinicopathologic characteristics in lung cancers [ 5 , 9 , 12 , 13 ]. These four studies have helped to identify subgroups of patients at high risk for LUAD progression.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have also revealed that genetic polymorphisms of MALAT1 have susceptibility to cancers [ 31 , 32 , 40 ]. In our study, the cohort of LUAD demographics and fundamental traits were comparable to those of previous Asian cohort [ 48 , 49 ]; these cohort also showed that LUAD patients with an EGFR mutation were more likely to be female, never-smokers, and to have better cell differentiation than the EGFR wild-type group. The absence of smoking was linked to the development of LUAD, whereas EGFR mutations were more common among never-smoker ( Table 1 ).…”
Section: Discussionsupporting
confidence: 81%
“…A higher frequency of IL-17A rs8193037GA and AA genotypes has been linked to a predisposition to NSCLC, as having the rs8193037A allele was associated with higher production of IL-17 ( Cheng et al, 2015a ). Moreover, patients carrying the T-allele of IL-17A rs8193036(C > T) had a higher risk of developing advanced stages of LUAD than those having the CC genotype of rs8193036, probably through inducing the overexpression of IL-17A ( Lee et al, 2021 ). These studies suggest that polymorphisms that cause IL-17 overexpression are associated with increased susceptibility and enhanced lung tumor progression.…”
Section: Innate Immunitymentioning
confidence: 99%